Neonatal Screening for Congenital Adrenal Hyperplasia in Turkey: Outcomes of Extended Pilot Study in 241,083 Infants - GÜRAN, TÜLAY (GALENOS YAYINCILIK, 2020)
Objective: Turkish Directorate of Public Health introduced the first pilot screening program for congenital adrenal hyperplasia (CAH) in four Turkish cities in 2017, and in 2018 extended the program, with a slight change in screening strategy, to fourteen cities. To evaluate the performance of the extended study and update previously reported outcomes. Methods: Retrospective, descriptive study. Neonates of >= 32 gestational weeks and >= 1500 gr birth weight from fourteen cities, born between May-December 2018, were included. Screening protocol included one sample, two-tier testing as applied in the previous pilot study. In the first step, 17 alpha-hydroxyprogesterone (17-OHP) was measured by fluoroimmunoassay in dried blood spots (DBS) obtained at 3-5 days of life. Cases with positive initial screening underwent second tier testing by steroid profiling in DBS using liquid chromatography-tandem mass spectrometry to measure 17-OHP, 21-deoxycortisol (21-S), cortisol (F), 11-deoxycortisol and androstenedione. The babies with a steroid ratio (21-S+ 17-OHP)/F of >= 0.7 (increased from >= 0.5 in the earlier pilot study) were referred to pediatric endocrinology clinics for diagnostic assessment. Results: In the evaluated period, 241,083 newborns were screened. 12,321 (5.11 %) required second-tier testing and 880 (0.36 %) were referred for clinical assessment, twenty of whom were diagnosed with CAH (10 females, 10 males). Sixteen were diagnosed as classical 21-hydroxylase deficiency (21-OHD) CAH (12 with salt-wasting and four with simple virilising CAH), and four cases were identified with 11 beta-OHD CAH. No case of salt-wasting CAH was missed by neonatal screening (sensitivity was 100 %). The incidence of classical 21-OHD and 11 beta-OHD in the screened population was 1:15,067 and 1:60,270, respectively. Conclusion: Turkish neonatal CAH screening effectively led to earlier diagnosis of 21-OHD and 11 beta-OHD, using steroid profiling as a second-tier test. This will result in improved care of these patients in the future.
Keywords: Neonatal screening; congenital adrenal hyperplasia; second-tier; steroid profiling; incidence; 11 beta-hydroxylase deficiency